PROBLEMS FACED BY PRIMARY SCHOOL TEACHERS IN IRBID GOVERNORATE AS PERCEIVED BY THE SCHOOL ADMINISTRATORS - Al-Jarrah, Fatima Nasser Khalifeh; Khasawneh, Hala Yousef Abdelrahman (European Scientific Journal, ESJ, 2013)
The Purpose of the present study is to identify the problems faced by primary school teachers from the viewpoints of school administrators based on such domains as: curriculum issues, students, local community, school building, facilities, scientific devices and to identify whether there is variation in the availability degree of such problems faced by teachers attributed to school administrative experience, or the academic qualification. A two-part questionnaire was developed based on (Alshamari, 1425 AH) to measure problems faced by primary school teachers within Irbid Governorate, and adjusted in light of the comments of the judges who validated the study instrument. The first scale measures the demographic characteristics of participants, whereas the second part measures problems faced by primary school teachers as perceived by the school administrators within Irbid Governorate. Sample (N=100) was representative of the public primary school administrators within Irbid Governorate. Results indicated problems faced by teachers; and found statistically significant differences (α=-0.05) attributed to the academic qualification effect on the problems faced that are related to the local community. Further, no statistically significant differences ((α=-0.05) were found attributed to experience effect on all domains. In light of the results, the authors called for increasing the funds allotted for school buildings, student numbers to accommodate classroom size, greater involvement of teachers in curriculum design and development. It is also recommended to set up remedial plans for poor achievers, help students pay greater attention to homework assignments, and invite parents to periodically hold meetings about the teaching process.